Nghiên cứu chế tạo và tính chất quang của các cấu trúc nano một chiều ZnS, ZnS/ZnO bằng phương pháp bốc bay nhiệt kết hợp với oxi hóa nhiệt trong môi trường khí oxi - Trung, Đỗ Quang; Tư, Nguyễn; Hùng, Nguyễn Duy; Tâm, Phương Đình; Huy, Phạm Thành (Vietnam Journal of Chemistry, 2014)
In this paper, we report on the controlled synthesis of one-dimensional ZnS and ZnS/ZnO nanostructures by thermal evaporation of ZnS powder combined with post oxidation in oxygen gas environment. Field emission scanning electron microscopy (FESEM) measurements showed that the products on the Si/Au wafers were ZnS nanowires and nanobelts, while ZnS nanorods were seen on the Si/SiO2 wafers. ZnS/ZnO nanoheterostructures were then obtained by oxidizing the corresponding ZnS nanostructures in pure oxygen gas environment at different temperatures. X-ray diffraction and photoluminescence (PL) measurement results indicate that the 1D ZnS nanostructures are hexagonal (Wurtzite) ZnS with rather good crystallity and can emit strong light in the visible. A very strong and broad green emission band with peak at around 500 nm was observed from the 1D ZnS nanostructures under 325 nm excitation of a Xenon lamp, at room temperature. At low temperature (10 K), the PL spectrum presents three emission bands peaking at 334, 380 and 500 nm, respectively for near band edge emission (NBE) of ZnS (334 nm), NBE of ZnO (380 nm) and defect-related emission in ZnS (500 nm). Depending on the oxidation temperature, 1D ZnS nanostructure could convert partly to ZnS/ZnO or completely to ZnO while keeping the shape of the starting 1D ZnS nanostructure. The mechanism of formation of 1D ZnS nanostructures and the ZnS to ZnO phase transition process will also be discussed. Keywords: ZnS/ZnO heterostructures, nanowires, nanobelts, nanorods, photoluminescence, one-dimensional nanostructures.